2016
DOI: 10.1248/bpb.b16-00427
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-Induced Thrombocytopenia Is Caused by Suppression of Platelet Production <i>via</i> Phosphorylation of Myosin Light Chain 2

Abstract: Linezolid (LZD) is an antimicrobial that is commonly used for treatment of vancomycin-resistantEnterococci and methicillin-resistant Staphylococcus aureus infections. However, the development of thrombocytopenia, one of the most frequent adverse side effects of this antimicrobial, can lead to discontinuation of LZD treatment. While clinical studies indicate that risk factors for the development of LZD-induced thrombocytopenia include treatment for >14 consecutive days, renal dysfunction, and chronic liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…For example, Tajima et al suggested that LDZ use for more than 14 days, renal dysfunction and chronic liver disease were risk factors linked to linezolid-induced thrombocytopenia. 9 In addition, a low baseline platelet count and body weight were associated with a decrease in the peripheral platelet count. 13 , 14 However, the main mechanism that regulates the pathogenesis of this adverse effect is still obscure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tajima et al suggested that LDZ use for more than 14 days, renal dysfunction and chronic liver disease were risk factors linked to linezolid-induced thrombocytopenia. 9 In addition, a low baseline platelet count and body weight were associated with a decrease in the peripheral platelet count. 13 , 14 However, the main mechanism that regulates the pathogenesis of this adverse effect is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Although linezolid use has advantages, it has been associated with adverse effects such as gastrointestinal disorders, hematological toxicity and cutaneous reactions. 8 , 9 The hematological reactions include anemia, eosinophilia, myelosuppression, neutropenia, cell aplasia and thrombocytopenia. 10 The normal peripheral platelet count is between 150 and 450 × 10 3 /mm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that LZD could cause the inhibition of the release of platelets from mature megakaryocytes, thus resulting in the development of thrombocytopenia. [ 17 ] Similarly, other studies suggested that thrombocytopenia was caused by the inhibition of platelet formation. [ 18 ] In contrast, a case report found an immune-mediated mechanism of platelet destruction may be the mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…The underlying mechanisms for thrombocytopenia (i.e., a circulating platelet count inferior to 150,000/mm 3 ) are increased platelet consumption/destruction or reduced platelet production. Linezolid, an antibiotic commonly used to treat vancomycin-resistant enterococci and methicillin-resistant Staphylococcus aureus infections, is known to induce myelosuppression, but is more frequently associated with thrombo- than pancytopenia (62). It was described that linezolid has no direct toxic effects on platelets and it does not affect the differentiation of hematopoietic stem cells, but via phosphorylation of an enzyme relevant for platelet release, it induces thrombocytopenia (62).…”
Section: Antibiotics and Their Influence On Clotting Platelet Functimentioning
confidence: 99%
“…Linezolid, an antibiotic commonly used to treat vancomycin-resistant enterococci and methicillin-resistant Staphylococcus aureus infections, is known to induce myelosuppression, but is more frequently associated with thrombo- than pancytopenia (62). It was described that linezolid has no direct toxic effects on platelets and it does not affect the differentiation of hematopoietic stem cells, but via phosphorylation of an enzyme relevant for platelet release, it induces thrombocytopenia (62). Although some influences of antibiotics on platelet functions were identified, the information on effects of antibiotic treatment on the coagulation system remains sparse.…”
Section: Antibiotics and Their Influence On Clotting Platelet Functimentioning
confidence: 99%